Garden pests (Texas Journal of Agriculture and Biological Sciences, 2023)
This paper provides information on the control of sucking pests in intensive fruit orchards by studying the bioecology of sucking pests such as aphids, aphids, spider mites, scale insects, mealybugs, etc.